Gaya Kognitif pada Kemampuan Pemecahan Masalah Matematis Siswa di Sekolah Dasar: Systematic Literature Review (SLR) - Fitria Khairani Salsabila; Anesa Surya (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Problem solving is one of the important aspects in learning mathematics. The purpose of this article is to analyze cognitive styles in the mathematical problem-solving abilities of elementary school students. The research method chosen in this study is the Systematic Literature Review (SLR) method by analyzing 5 selected articles that meet the criteria. The literature searched for was journal articles published in the period 2017 - 2024 and using the Google Scholar database. The results of the study showed that the mathematical problem-solving abilities of elementary school students vary depending on the cognitive style of each student. Students with a field independent cognitive style are more analytical while students with a field dependent cognitive style have a global way of thinking. Thus, it is important for elementary school teachers and schools to develop mathematical problem-solving abilities by paying attention to the cognitive style of students.Pemecahan masalah merupakan salah satu aspek yang penting dalam pembelajaran matematika. Penulisan artikel ini bertujuan untuk menganalisis gaya kognitif pada kemampuan pemecahan masalah matematis siswa sekolah dasar. Metode penelitian yang dipilih dalam penelitian ini adalah metode Systematic Literature Review (SLR) dengan menganalisis 5 artikel terpilih yang memenuhi kriteria. Literatur yang dicari adalah artikel jurnal yang diterbitkan pada periode 2017 – 2024 dan menggunakan database Google Scholar. Hasil penelitian menunjukkan bahwa kemampuan pemecahan masalah matematis siswa sekolah dasar berbeda-beda tergantung pada gaya kognitif masing-masing peserta didik. Peserta didik dengan gaya kognitif field independent lebih analitik sedangkan siswa yang memiliki gaya kognitif field dependent memiliki cara berpikir yang global. Dengan demikian, guru sekolah dasar dan sekolah penting untuk mengembangkan kemampuan pemecahan masalah matematis dengan memperhatikan gaya kognitif yang dimiliki siswa.